To buy or not to buy: The liability and attitudes of selected consumers towards purchasing pirated discs - Ampatuan, Lady Sha-honey A. (Animo Repository, 2015)
Selling of counterfeit and pirated goods is rampant around the world. Despite the enactment of the Intellectual Property Code and other related laws, piracy remained entrenched in the country. The rampant music and film piracy has been identified as a major factor behind the ongoing attrition in the local industry. Every year the industry is losing millions because of piracy. So, researcher believed that this poses a legal issue and management issue. The legal issue is whether buyers or consumers of pirated goods have liability under the Anti-Fencing Law. Because, according to the IP Law, copyright infringment, occurs when a copyrighted work is reproduced, distributed, performed, publicly displayed, or made into a derivative work without the permission of the copyright owner (IP Code, 1998). On the other hand, the crime of fencing is committed when a person who, with intent to gain for himself or for another, shall buy, receive, possess, keep, acquire, conceal, sell or dispose of, or shall buy and sell, or in any other manner deal in any article, item, object or anything of value which he knows, or should be known to him, to have been derived from the proceeds of the crime of robbery or theft (Anti-Fencing Law, 1979). The management